Discrepant Data and Improbable Results: An Examination of Vohs, Mead, and Goode (2006). Issue 4 (4th July 2019) - Rohrer, Doug; Pashler, Harold; Harris, Christine R.
Abstract: A highly cited article by Vohs, Mead, and Goode (2006) reported several experiments in which an incidental reminder of money produced large effects on subsequent behaviors unrelated to money. We attempted 2 high-powered direct replications of the first experiment, which found that money-primed subjects worked on a puzzle nearly twice as long as controls before quitting. The replication studies showed no evidence of money priming. Moreover, 25% of the subjects in our studies solved the puzzle correctly or incorrectly, whereas none reportedly did so in the original study. We also list anomalies in the reported results of the original study.